Collective conceptualization of parental support of dual career athletes: The EMPATIA framework - Kinga Varga; Ciaran MacDonncha; Laura Capranica; Mojca Doupona (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
This study aimed to use a concept mapping methodology (Trochim, 1986b) to develop a European framework of the needs of parents and guardians for supporting athletes combining sport and education (dual career). By means of a concept mapping methodology, we gathered 337 French, Irish, Italian, Portuguese, and Slovenian parents' demographical data linked with their sorted and rated data of the 80 potential statements associated to parenting dual career athletes. In synthesizing the opinions, experience and needs of parents and guardians of dual career athletes, concept mapping served as a unique integration of qualitative and quantitative methods. The present framework provided sound theoretical underpinnings as well as quantitative basis to inform the development of educational platforms for empowering parenting dual carrier athletes, as well as be a foundation for future Pan-European dual career research on how these statements interact with each other, in different European contexts.
Keywords: C31; C61; I21; 330; Parenting student-athletes; Concept mapping; Dual Career of athletes; European framework